Gentrification of peri-urban spaces in France: The surroundings of Nancy; Gentrifizierung in periurbanen Räumen Frankreichs: Am Beispiel des Umlandes von Nancy - Hervé Marchal; Jean-Marc Stébé; Florian Weber (Raumforschung und Raumordnung / Spatial Research and Planning, 2019)
The process of gentrification in the peri-urban districts of French cities has scarcely been touched upon in recent research, which has hitherto seen the phenomenon as typically associated with core urban areas. The tendency has been to view the periphery through the lens of the social crisis of the banlieues. In contrast, the present article focuses on gentrification in the metropolitan area of Nancy (Grand Est region) as a development that also plays a role in municipalities around major cities and especially around regional metropolitan centres. Starting with a survey of current research approaches, the article first pinpoints some gaps and methodological imbalances that need to be tackled, before embarking on the case study of peri-urban Nancy. Statistical data and empirical surveys in the form of qualitative interviews indicate how Nancy's peri-urban districts have developed a logic of separation, exclusion and social decoupling ‒ typical features of gentrification ‒ particularly in connection with the construction of new single-family houses as a supplement to existing residential stock. Key questions here concern individual motives for choosing a particular residential location, and the creeping "segregation from above" that accompanies this process. The image of France's peri-urban spaces that arises from this study stands in explicit contrast to the received, markedly negative connotations of the "urban periphery". – – Gentrifizierungsprozesse in periurbanen Räumen Frankreichs fanden in der Forschung bisher kaum Beachtung; sie wurden als naheliegende Prozesse in Kernstädten verstanden und untersucht. Zudem wurde eher die Krise der Vorstädte, der banlieues, beachtet, womit Stigmatisierung und Ausgrenzung analyseleitend wurden. Im vorliegenden Beitrag wird nun hingegen am Beispiel des Umlandes der Metropole Nancy (Region Grand Est) Gentrifizierung als Entwicklung herausgestellt, die sich ebenfalls als konstitutiv für periurbane Räume und damit kleinere Umlandgemeinden von Städten bzw. insbesondere Metropolen andeutet. Vor dem Hintergrund einer Beleuchtung bisheriger Forschungszugänge werden zunächst Forschungslücken herausgearbeitet. Anhand der Auswertung statistischer Daten und empirischer Erhebungen mittels qualitativer Interviews im Umland von Nancy wird im Anschluss fallstudienbezogen gezeigt, wie sich periurbane Gemeinden, insbesondere in Verbindung mit dem Bau neuer Einfamilienhäuser in Ergänzung zu bestehender Bausubstanz, in eine Gentrifizierungslogik der Ab- und Ausgrenzung einschreiben, welche individuellen Beweggründe Wohnstandortwahlen beeinflussen und wie sich eine "Segregation von oben" immer mehr ausbreitet. Es entsteht so ein verändertes Bild periurbaner Räume, das im expliziten Kontrast zu einer eher negativ konnotierten "urbanen Peripherie" steht.
Keywords: 710; Peri-urban spaces; peri-urban gentrification; heterogenization; metropolitan area of Nancy (Lorraine); qualitative approach; Periurbane Räume; Periurbane Gentrifizierung; Heterogenisierung; Großraum Nancy (Lothringen); Qualitativer Zugang